2014
DOI: 10.1016/j.virol.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Viruses infecting marine picoplancton encode functional potassium ion channels

Abstract: Phycodnaviruses are dsDNA viruses, which infect algae. Their large genomes encode many gene products, like small K(+) channels, with homologs in prokaryotes and eukaryotes. Screening for K(+) channels revealed their abundance in viruses from fresh-water habitats. Recent sequencing of viruses from marine algae or from salt water in Antarctica revealed sequences with the predicted characteristics of K(+) channels but with some unexpected features. Two genes encode either 78 or 79 amino acid proteins, which are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…We have previously reported that some viruses, which infect unicellular marine algae, also encode genes with the hallmarks of K + channels (Siotto et al, 2014). An initial functional testing of some of these proteins revealed that they have non-canonical architectures in their TM domains, but that they still form functional K + channels (Siotto et al, 2014). Here we perform a comparative examination of K + channels, which are similar in their structure but fundamentally different in their voltage dependency.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…We have previously reported that some viruses, which infect unicellular marine algae, also encode genes with the hallmarks of K + channels (Siotto et al, 2014). An initial functional testing of some of these proteins revealed that they have non-canonical architectures in their TM domains, but that they still form functional K + channels (Siotto et al, 2014). Here we perform a comparative examination of K + channels, which are similar in their structure but fundamentally different in their voltage dependency.…”
Section: Introductionmentioning
confidence: 95%
“…Here we further exploit the diversity of viral K + channel genes by screening viral K + channels from a marine habitat. We have previously reported that some viruses, which infect unicellular marine algae, also encode genes with the hallmarks of K + channels (Siotto et al, 2014). An initial functional testing of some of these proteins revealed that they have non-canonical architectures in their TM domains, but that they still form functional K + channels (Siotto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[105][106][107][108] Their structure is that of an extremely reduced Kir channel: 2 transmembrane helices per monomer are connected by a short loop containing the consensus K C selectivity filter sequence and the characteristic pore helix. The protein does not contain any cytosolic or extracellular domains and it is fully embedded in the lipid bilayer.…”
Section: Channelmentioning
confidence: 99%
“…Each monomer is made of 2 transmembrane domains, which are connected by the pore helices. [105][106][107][108] A further advantage of these channels is that members differ only by a few amino acids, but show quite different functional properties. This guides the experimenter to those residues, which are crucial for function.…”
Section: Supplementing 2-dimensional Dwell-time Analysis By the Analymentioning
confidence: 99%
“…In contrast, the flexible pan-genome comprises many genes of unknown function, but also contains some metabolic genes similar to the auxiliary metabolic genes (AMGs) found in cyanophages [17]. The genomes vary in the transfer RNAs (tRNAs) [12] and K + channels [18] that are encoded. Additionally, Ostreococcus viruses possess genes of presumed cellular origin, some with homologues in their hosts.…”
Section: Introductionmentioning
confidence: 99%